The 6th International Evidence Based Library and Information Practice Conference (EBLIP6): Conference report and reflections - Katrina Hall (Evidence Based Library and Information Practice, 2011)
BRETTLE, A., GRANT, M., FRASER, K., DALZIEL, K., GARDOIS, P., LEWIS, S., KAALVIK, H., ELDREDGE, J.. The 6th International Evidence Based Library and Information Practice Conference (EBLIP6): Conference Report and Reflections. Evidence Based Library and Information Practice, North America, 6, dec. 2011. Available at: <http://ejournals.library.ualberta.ca/index.php/EBLIP/article/view/12264>. Date accessed: 19 Dec. 2011.